Meningkatkan Hasil Belajar Matematika Materi Penyajian Data melalui Model Pembelajaran Student Teams Achievement Divisions di Kelas VII-2 Madrasah Tsanawiyah Negeri 2 Bogor - Nuryeti (Institut Agama Islam Sahid (INAIS) Bogor, 2020)
Based on experience, the problem experienced in teaching and learning activities is that there are still many students from Madrasah Tsanawiyah (MTs) National 2 Bogar who get grade under KKM, mathematics is considered a difficult subject, there are many formulas, the teacher thinks students have the same ability, in the teaching and learning process communication occurs in one direction, namely from teacher to student, the teacher has not implemented a learning model that allows interaction between students and students as well as students and teachers. The Student Teams Achievement Divisions (STAD) learning model is applied to group different abilities so that it allows interaction between teachers and students to occur, students and students actively so that it is hoped that students who are smart will help students who are less proficient. This class action research aims to find out whether the application of the STAD learning model can improve students' learning outcomes in class VII-2 MTs Negeri 2 Bogar. The procedure carried out refers to the stages 1) Planning, 2) Implementation of actions, 3) Observation, and 4) Reflection. Results of the quiz in cycle 1 of the first meeting the number of students who scored above the KKM (70) was 34 students, namely 94.44%. The percentage of quiz scores achieved in the 1st cycle 2nd meeting is 100%. The value of quiz 1 and 2 experienced an increase of 5.56%. In the 2nd cycle of the first meeting , the number of students who scored above KKM (70) was 39 students, which is 100%. Thus the STAD learning model can improve the mathematics learning outcomes of data presentation material for MTs Negeri 2 Bogar students.